Xanthine Oxidase Drives Hemolysis and Vascular Malfunction in Sickle Cell Disease. Issue 2 (February 2021) - Schmidt, Heidi M.; Wood, Katherine C.; Lewis, Sara E.; Hahn, Scott A.; Williams, Xena M.; McMahon, Brenda; Baust, Jeffrey J.; Yuan, Shuai; Bachman, Timothy N.; Wang, Yekai; Oh, Joo-Yeun; Ghosh, Samit; et al.
Abstract : Objective: Chronic hemolysis is a hallmark of sickle cell disease (SCD) and a driver of vasculopathy; however, the mechanisms contributing to hemolysis remain incompletely understood. Although XO (xanthine oxidase) activity has been shown to be elevated in SCD, its role remains unknown. XO binds endothelium and generates oxidants as a byproduct of hypoxanthine and xanthine catabolism. We hypothesized that XO inhibition decreases oxidant production leading to less hemolysis. Approach and Results: Wild-type mice were bone marrow transplanted with control (AA) or sickle (SS) Townes bone marrow. After 12 weeks, mice were treated with 10 mg/kg per day of febuxostat (Uloric), Food and Drug Administration–approved XO inhibitor, for 10 weeks. Hematologic analysis demonstrated increased hematocrit, cellular hemoglobin, and red blood cells, with no change in reticulocyte percentage. Significant decreases in cell-free hemoglobin and increases in haptoglobin suggest XO inhibition decreased hemolysis. Myographic studies demonstrated improved pulmonary vascular dilation and blunted constriction, indicating improved pulmonary vasoreactivity, whereas pulmonary pressure and cardiac function were unaffected. The role of hepatic XO in SCD was evaluated by bone marrow transplanting hepatocyte-specific XO knockout mice with SS Townes bone marrow. However, hepatocyte-specific XO knockout, which results in >50% diminution in circulating XO, did not affect hemolysis levels or vascular function, suggesting hepatocyte-derived elevation of circulating XO is not the driver of hemolysis in SCD. Conclusions: Ten weeks of febuxostat treatment significantly decreased hemolysis and improved pulmonary vasoreactivity in a mouse model of SCD. Although hepatic XO accounts for >50% of circulating XO, it is not the source of XO driving hemolysis in SCD. Abstract : Supplemental Digital Content is available in the text.